Biopharmacology of Enzyme Conjugates: Vasoprotective Activity of Supramolecular Superoxide Dismutase-Chondroitin Sulfate-Catalase Derivative - Maksimenko, A.V. (A.I. Gordeyev, 2010)
Bienzyme conjugate was obtained by the covalent connection of superoxide dismutase with catalase through endothelial glycocalyx glycosaminoglycan – chondroitin sulfate (SOD-CHS-CAT). This SOD-CHS-CAT conjugate has vasoprotective activity in respect to platelet interactions, tonus of the ring arterial fragment of a rat blood vessel, as well as normalization of hemodynamic parameters in rats and rabbits in conditions of oxidative stress caused by the administration of hydrogen peroxide. The SOD-CHS-CAT conjugate had antiplatelet potential due to its antiaggregation action manifested through the combination of enzyme activities and an acquired supramolecular structure. The influence on arterial fragment tonus was equivalent for SOD and CAT in native and conjugated form. Blood pressure and heart rate were significant and effectively normalized with SOD-CHS-CAT conjugate in rats and rabbits (after hydrogen peroxide administration as a perturbance stimulus). We have discovered the possibility of using the antioxidant bienzyme conjugate in chronic prophylaxis. It is important for a real development of the oral form of the SOD-CHS-CAT conjugate. These results indicate that the development of enzyme conjugates can be medically significant, as a promising approach for the creation of new drugs.